2016
DOI: 10.1371/journal.pone.0150605
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomic Profiling of Divergent Phenotypes for Water Holding Capacity across the Post Mortem Ageing Period in Porcine Muscle Exudate

Abstract: Two dimensional Difference Gel Electrophoresis (2-D DIGE) and mass spectrometry were applied to investigate the changes in metabolic proteins that occur over a seven day (day 1, 3 and 7) post mortem ageing period in porcine centrifugal exudate from divergent meat quality phenotypes. The objectives of the research were to enhance our understanding of the phenotype (water holding capacity) and search for biomarkers of this economically significant pork quality attribute. Major changes in protein abundance across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 71 publications
(125 reference statements)
3
21
0
Order By: Relevance
“…Except potential candidate genes listed above, we also confirmed several known candidate genes influencing drip loss reported in the previous studies. Heat shock proteins (HSPs) HSPs belong to stress related proteins, and have been reported as potential biomarkers for several meat quality traits (WHC, tenderness, and colour) [27, 28]. In this study, several HSP genes, like HSPB1 , HSPH1 , HSPB7 and HSPA1L were found to not only differently express between the low and high drip loss groups, but significantly correlated in the correlation analysis in the 28 Duroc pigs.…”
Section: Discussionmentioning
confidence: 65%
“…Except potential candidate genes listed above, we also confirmed several known candidate genes influencing drip loss reported in the previous studies. Heat shock proteins (HSPs) HSPs belong to stress related proteins, and have been reported as potential biomarkers for several meat quality traits (WHC, tenderness, and colour) [27, 28]. In this study, several HSP genes, like HSPB1 , HSPH1 , HSPB7 and HSPA1L were found to not only differently express between the low and high drip loss groups, but significantly correlated in the correlation analysis in the 28 Duroc pigs.…”
Section: Discussionmentioning
confidence: 65%
“…Consistently, the present study found that drip loss and cooking loss were quadratically decreased by dietary L ‐theanine supplementation, which is consistent with Saeed et al () who reported that WHC of breast and thigh muscle was improved by L ‐theanine. Drip loss of meat is associated with the ultimate pH, and a lower ultimate pH is thought to lead to higher drip loss (Di Luca, Hamill, Mullen, Slavov, & Elia, ; Liu et al, ). It is therefore not surprising that pH 24h were quadratically increased by L ‐theanine along with the decreased drip loss in the present study and the results of Saeed et al().…”
Section: Discussionmentioning
confidence: 99%
“…Proteomics notably, which corresponds to the large-scale study of the proteome of a tissue at a given moment and condition, was applied in the field of meat quality with several objectives (for review see (Almeida et al, 2015;). For example, proteomics was used to study meat tenderness variability (Morzel, Terlouw, Chambon, Micol, & Picard, 2008), to investigate technological meat quality traits likely water holding capacity, drip loss and pH (Di Luca, Hamill, Mullen, Slavov, & Elia, 2016) and also to study meat color stability and development (Hwang, Park, Kim, Cho, & Lee, 2005). The use of proteomic tools (two-dimensional electrophoresis and mass spectrometry) to study the muscle-specificity in beef color stability is recent and was first applied by (Joseph, Suman, Rentfrow, Li, & Beach, 2012).…”
Section: Introductionmentioning
confidence: 99%